Exploring the anti-colon cancer potential of Polygonum minus: integrating in vitro and in silico studies - Yang, Zhongming; Yang, Zhongguo; Abu Bakar, Md Zuki; Deng, Xi (Elsevier Ltd, 2025)
Polygonum minus Huds (PM), commonly known as “laksa leaves”, is a valuable aromatic plant used in food and traditional medicine, particularly in Southeast Asia. This study aimed to fractionate PM hexane leaf extract to evaluate the anti-colon cancer activity of its fractions and identify the active compounds responsible for its therapeutic potential. Water, methanol, and acetonitrile were utilized for the liquid-liquid partitioning of PM hexane extracts. The safety and cytotoxicity of the resulting fractions were assessed to identify the most promising active fraction. Phytochemical profiling of the active fraction was further analyzed using GC-MS, and in silico analyses of its major phytochemicals were performed to screen the phytochemicals for application potential. The results showed that the water fraction was the most toxic to brine shrimp, while the methanol and acetonitrile fractions were favorably safe, and the hexane fraction was non-toxic. Moreover, the acetonitrile fraction (PM-H-A) exhibited significant cytotoxic effects on CT26 colon cancer cells. This was validated by dose-dependent morphological changes, colony formation inhibition, apoptosis induction, cell cycle arrest, and cell migration suppression in CT26 cells. Notably, PM-H-A also demonstrated inhibitory effects in the 3D culture model of CT26 cells. GC-MS analysis identified nine major phytochemicals in PM-H-A, with the in silico predictions showing remarkable cytotoxicity of these phytochemicals against colon cancer cells, particularly undecanoic acid, dodecanoic acid, and 9,12,15-octadecatrienoic acid. Mechanistic studies revealed that these compounds may exert their anticancer effects by targeting lipid metabolism and inflammation pathways. Among them, 9,12,15-octadecatrienoic acid stands out due to its favorable pharmacokinetics and safety. Overall, 9,12,15-octadecatrienoic acid holds pronounced promise as a therapeutic agent for colon cancer, warranting further investigation of its clinical potential.